Recurring Themes Across Fractal Issues Facing International Students: A Thematic Analysis of 2016 Dissertations and Theses - Bista, Krishna; Gaulee, Utam (Journal of International Students, 2017)
This section shares recent dissertations and theses with the Journal of International Students readers. There were about 139 graduate dissertations and theses related to the issues and challenges of international students in 2016. The complete versions of these selected dissertations are available in the ProQuest, Michigan-based electronic publisher. ProQuest Dissertations & Theses Global is the world's most comprehensive collection of dissertations and theses from around the world, spanning from 1743 to the present day. This database has found 17,164 results from 1922-2018 while searching the keywords “international student” in its search engine.